Processing panoramic images in heritage. Jaen Cathedral - Gregorio Soria; Lidia Ortega; Francisco R. Feito; Inmaculada Barroso (Virtual Archaeology Review)
A spherical photo is an image that it can show a scene and the user can interact with its. We are working in the Jaén’s cathedral. We are giving the possibility of a virtual visit with good results in many points at this place. We labored with a camera called Lady Bug 2. It can take spherical photo very easy. We used some web tools where we share all ours work.